Case report: Therapeutic potential of T-VEC in combination with MEK inhibitors in melanoma patients with NRAS mutation - Simon, Sonja C. S.; Müller, Verena; Utikal, Jochen S. (Frontiers in Oncology, 2023)
Mutations in the NRAS gene are common alterations in malignant melanoma. However, there are no specific treatment options approved for NRAS-mutated melanoma patients besides immune checkpoint inhibition. Since preclinical data suggests a synergistic effect of a MEK inhibitor (MEKi) and the oncolytic virus talimogene laherparepvec (T-VEC), we have treated three melanoma patients with this combination. All of the three patients had been suffering from recurring cutaneous and subcutaneous in-transit metastases. Upon treatment one patient (case 1) presented full regression of locoregional metastases and remained progression-free until date, for almost three years. The second patient (case 2) showed a partial regression of painful gluteal satellite metastases but died from brain metastases. The third patient (case 3) showed a durable response of locoregional metastases for seven months. The combination treatment was well tolerated with common adverse events known for each single agent. This report is the first case series presenting a clinical benefit of the combined T-VEC and MEKi treatment. We suggest the combination of T-VEC and MEKi as an off-label treatment option for patients with NRAS mutations, especially with recurrent in-transit or satellite metastases.